Sistem Kewarisan Adat Masyarakat Muslim Suku Tengger Perspektif Hukum Islam - Raja Ritonga (Program Studi Hukum Keluarga Islam STAIN Mandailing Natal, 2020)
This research describes about inheritance system to the moslem society of Tengger's family and analizes the values of tradition law on Islamic law perspective. This research uses a qualitative- descriptive design. A researcher acts as a collector data in the field by observing and interviewing. Beside it, a researcher does a librarian study about the references of tradition law and Islamic law. The result ofanalysis on judirical observation is about the appropriateness value to the spirit Islamic soul. As like the billaterial principal is descent principle that computing family's relationship between man and woman. While the meaning of individual principle is inheritance member has a right to get inheritance individually. As for normative observation, it is found that many rules are not in Islamic law line. For instance, the structure inheritance, time of dividing inheritance, prerequrement,pillar,the cause and the quantity. Islamic law is dominated by tradition law,especially on the inheritance case. On practicing, parent have a certain rule about inheritance since dividing,sizing and changing inheritance. Keywords: Tradition inheritance, Tengger’s family